2021
DOI: 10.1590/0103-8478cr20190495
|View full text |Cite
|
Sign up to set email alerts
|

Seedling length and soybean seed vigor

Abstract: The differentiation of seedling growth and development is the result of the vigor level of the seed lot. Because of this, knowing the seedling growth curve is essential for the evaluation of the seedling length test, to be carried out at the moment when any differences in vigor really manifest, thus being able to reduce the time of evaluation of the test. In this research, the objective was to determine the most efficient time interval to perform the seedling length test in soybean seeds, depending on the vigo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Differences in seed vigor can lead to the formation of seedlings with greater unevenness, due to the reduced capacity to use the reserves present in the embryo's structures, in fact affecting the growth rate and dry mass production, due to the inequality in the issue of growth of the plant between the different vigor levels (Meneguzzo et al, 2021). Only one of the 14 seed lots presented a significant response in the percentage of normal seedlings to KNO 3 (Table 2); these seeds probably had low vigor due to the storage time.…”
Section: Resultsmentioning
confidence: 99%
“…Differences in seed vigor can lead to the formation of seedlings with greater unevenness, due to the reduced capacity to use the reserves present in the embryo's structures, in fact affecting the growth rate and dry mass production, due to the inequality in the issue of growth of the plant between the different vigor levels (Meneguzzo et al, 2021). Only one of the 14 seed lots presented a significant response in the percentage of normal seedlings to KNO 3 (Table 2); these seeds probably had low vigor due to the storage time.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies identified moisture retention capacity of seeds, germination rates, uniformity and growth as the main components of seed vigour, that are also negatively influenced by seed storage conditions ( Egli et al., 1990 ; Finch-Savage and Bassel, 2016 ; Ebone et al., 2020 ; Meneguzzo et al., 2021 ). These components are said to play a key role in germination and seedling development.…”
Section: Introductionmentioning
confidence: 99%
“…These components are said to play a key role in germination and seedling development. Meneguzzo et al. (2021) reported differentiation of seedling growth and development as a result of vigour levels of seed lots in soybean cultivar 5855 RSF IPRO.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During storage, soybean seeds undergo metabolic processes that can lead to deterioration. The consumption of seed reserves, such as sugars, proteins, and oils, diminishes germination rates and seed vigor, directly impacting the successful establishment of the crop (Mahjabin et al, 2015;Meneguzzo et al, 2021). These metabolic reactions are boosted under field conditions, such as heat, drought, and other environmental factors that reduce seed quality, viability, and vigor (Rao et al, 2023).…”
Section: Introductionmentioning
confidence: 99%